Umbilical Granuloma in an Eight Year Child - George, Susan Mary (Journal of Nepal Paediatric Society, 2017)
Discharging lesions in the umbilical region are rare but well known in neonatal period. Omphalitis, umbilical granuloma, patent urachus and persistent vitelo-intestinal duct are some of the commonest causes. If such a lesion is found in an older child, a careful detailed history and examination of the lesion can give clue to the diagnosis. We present one such case of a rare case of umbilical granuloma.